2022
DOI: 10.3389/fphys.2021.808541
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ablation Efficiency in PVI Guided by Contact Force and Local Impedance: Chronic Canine Model

Abstract: Background: The purpose of this study was to assess the effect local impedance (LI) has on an ablation workflow when combined with a contact force (CF) ablation catheter.Methods: Left pulmonary vein isolation was performed in an in vivo canine model (N = 8) using a nominal (30 W) or an elevated (50 W) power strategy with a CF catheter. The catheter was enabled to measure LI prior to and during ablation. LI was visible for only one of the vein isolations.Results: Chronic block was achieved in all animals when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Baseline LI showed the highest correlation to ΔLI which is in line with recently published experimental (Garrott et al, 2020;Gutbrod et al, 2022) and clinical studies (Martin et al, 2018;Gunawardene et al, 2019;Szegedi et al, 2021;Matsuura et al, 2022;Solimene et al, 2022). Furthermore, according to our results combined mean CF and baseline LI was the best predictor for a ΔLI > 20 Ω in comparison to applied mean CF or baseline LI alone.…”
Section: Biophysical Rationale Of Combined Force and Impedance Assess...supporting
confidence: 91%
See 1 more Smart Citation
“…Baseline LI showed the highest correlation to ΔLI which is in line with recently published experimental (Garrott et al, 2020;Gutbrod et al, 2022) and clinical studies (Martin et al, 2018;Gunawardene et al, 2019;Szegedi et al, 2021;Matsuura et al, 2022;Solimene et al, 2022). Furthermore, according to our results combined mean CF and baseline LI was the best predictor for a ΔLI > 20 Ω in comparison to applied mean CF or baseline LI alone.…”
Section: Biophysical Rationale Of Combined Force and Impedance Assess...supporting
confidence: 91%
“…Several experimental and clinical studies have recently been published reporting experiences of combined CF and LI assessment during index AF ablation (Szegedi et al, 2021;Gutbrod et al, 2022;Solimene et al, 2022;Yasumoto et al, Frontiers in Physiology frontiersin.org 2022). Single-shot devices have seen increased usage for index AF ablations in recent years (Mulder et al, 2021).…”
Section: Value Of Combined Force and Impedance Assessment During Repe...mentioning
confidence: 99%
“…Gutbrod et al ( 13 ) showed that the local impedance of the tissue is significantly higher when CF is at least 5 g compared to those with an applied CF below 5 g. However, when comparing different CF values above 5 g, they found no significant difference in local impedance. This suggests that once CF reaches a value of 5 g, stable contact with the tissue is achieved, and a further increase in CF does not result in significantly greater stability ( 13 ). Consistent with this, we also found that a CF ≥ 5 g results in significantly higher maximum temperatures during ablation ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was clearly showed recently that changes in generator impedance show a weak correlation with lesion formation (26). Gutbrod et al (13) showed that the local impedance of the tissue is significantly higher when CF is at least 5 g compared to those with an applied CF below 5 g. However, when comparing different CF values above 5 g, they found no significant difference in local impedance. This suggests that once CF reaches a value of 5 g, stable contact with the tissue is achieved, and a further increase in CF does not result in significantly greater stability (13).…”
Section: Parameters Used For Assessing Efficacy and Safety Of Ablatio...mentioning
confidence: 98%
See 1 more Smart Citation